2018
DOI: 10.1088/1361-6579/aac9a9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of heart rate and inter-beat intervals with wrist plethysmography in patients with atrial fibrillation

Abstract: Results suggest that wrist PPG measurement allows accurate HR and beat-to-beat HR monitoring also in AF patients, and could be used for differentiating between SR and AF with very good sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…It has been shown previously that IBI extracted from PPG corresponds closely with IBI extracted from ECG [67], [68]. This allowed us to exploit existing high-quality ECG datasets for this study.…”
Section: Discussionmentioning
confidence: 56%
“…It has been shown previously that IBI extracted from PPG corresponds closely with IBI extracted from ECG [67], [68]. This allowed us to exploit existing high-quality ECG datasets for this study.…”
Section: Discussionmentioning
confidence: 56%
“…Most of the studies include fewer than 100 volunteers. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Six studies had a study population of more than 100 subjects [35][36][37][38][39][40] ; the largest monitored 1617 volunteers in an ambulatory setting. 36 Rhythm characteristics in the study populations varied among studies.…”
Section: Study Populationsmentioning
confidence: 99%
“…Edgerton and colleagues 16 suggested that 7-days' monitoring after ablation of AF was ideal, but the optimal monitoring period after cardiac surgery without ablation has not been defined. Evolving developments in wearable technology 17,18 may represent an opportunity for more convenient ambulatory monitoring but need further validation of their accuracy. Patients with existing cardiac devices represent an opportunity to study the incidence of POAF by routinely interrogating such devices postoperatively.…”
Section: Future Directions: Opportunitiesmentioning
confidence: 99%